Measurement properties of remotely or self-administered physical performance measures to assess mobility: a systematic review protocol. (4th March 2022) - Morgan, Ashley; Bégin, Diane; Heisz, Jennifer; Tang, Ada; Thabane, Lehana; Richardson, Julie
Abstract: Background: Physical performance measures assessing mobility are important tools for assessing current functional status, predicting future functional status, and monitoring change. To respond to the increased necessity to conduct research and care remotely and self-monitor one's health status, there is a need for reliable, valid, and responsive measures that can be self or remotely administered. Objectives: To evaluate (i) the test procedures and population suitability of remotely or self-administered lower extremity performance measures and (ii) the measurement properties of scores for these measures. Methods: This review will include quantitative studies with adult participants (≥ 18 years) who are living independently in the community. For the purposes of this review, mobility is defined as the ability to move by changing body position or location or transferring from one place to another as per the International Classification of Functioning, Disability and Health (ICF) framework. Five databases; MEDLINE, EMBASE, CINAHL, AMED and Cochrane CENTRAL will be searched to identify relevant studies. Reference lists of relevant studies will be hand-searched to identify additional eligible studies. Title and abstracts screening, full text screening and data extraction will be completed independently by two reviewers. Results will be compared against COnsensus-based Standards for the selection of health Measurement Instruments' (COSMIN) criteria for measurement properties which provide a sufficient, insufficient, or indeterminate rating based on whether a previously defined hypothesis (set by research team or by COSMIN). The quality of each study will be assessed by two independent reviewers using COSMIN's Risk of Bias tool.